Transportation, water and environmental geotechnics. proceedings of Indian Geotechnical Conference 2020 - Reddy, C. N. V. Satyanarayana; Saride, Sireesh; Haldar, Sumanta (Lecture Notes in Mechanical Engineering (LNME), 2021)
This book comprises select proceedings of the Indian Geotechnical Conference 2020 (IGC2020) focusing on emerging opportunities and challenges in the field of transportation geotechnics, scour and erosion, offshore geotechnics, and environmental geotechnology. The contents will be useful to researchers, educators, practitioners and policy makers alike.